Qasr al-Bint Temple “Sanctuary of the Nabataeans” - Tashman, Laura H. (Sapiens ubique civis, 2023)
Qasr al-Bint Temple is one of the best-preserved freestanding structures in Petra beside it is the main temple of the ancient city. The Nabataeans built this Temple at about the same time as the famous Al-Khazneh (Treasury) was built, in the second half of the reign of King Aretas IV (ruled 9 BC–40 AD). I can surely say that this Temple is an outstanding and unique example of the fusion of Greco-Roman and Eastern elements in Nabataean architecture, which motivates scholars to study and write about it. The Nabataean’s architecture, culture and religion still fascinate every scholar whenever they discover something new about them. Unfortunately, the Nabataeans did not leave many inscriptions that reveal all details of their life, but they left the most amazing archeological remains that will always be impressive and provide the motivation to learn and dig more to reveal more about their mysteries. In this paper, I will write in general about the Nabataeans origin, their settlement and location and their temples. Then I will write in detail about Qasr al-Bint Temple which I will focus on in my paper, regarding its location, most important features and function.